Gastrointestinal parasites in Macaca fascicularis living in two urban areas of Malaysia - Sharifah Aminah, Tuan Said; Jaya Vejayan, Palliah; Nur A’fiefah, Mohd Zulkeffli; Hani Kartini, Agustar (University of Malaya, 2022)
Macaca fascicularisor commonly known as long-tailed macaques,are nonhuman primates that are increasingly vulnerable in becoming natural reservoirs for many microorganisms including gastrointestinal (GI) parasites, largely due to anthropogenic activities. This study was conducted to detect and compare GI parasites in M. fascicularisfound in densely urbanized settings. The fecal samples of the long-tailed macaques were collected at a public university campus (Universiti Kebangsaan Malaysia, Bangi) and a tourist site (Bukit Melawati, Kuala Selangor). A total of 80 fecal samples were collected: 50 at the university campus, and the remaining samples from the tourist site. The fecal samples were processed by flotation techniques to include the GI parasites and then were subjected tomorphological analysis to identify important taxonomy keys under microscopic magnification. A total of 139 parasites were identified from both locations and classified into 5 phylums and 17 families. Among the 139 parasites, 33 parasites were grouped into 6 genus of GI parasites. Among the gastrointestinal parasites that were identified from both study sites, three parasites were zoonotic namely Strongyloidsspp., Trichostrongylusspp.and Trichurisspp.Results showed that the diversity index of GI parasites was higher at the university campus compared to the tourist site with Simpson’s Index values of 0.953 and 0.880, respectively, while the Shannon’s Index values were 3.282 and 2.399, respectively. This research revealed that there are more parasite infections in the long-tailed macaques in the campus surroundings compared to those found in the tourist site. Therefore, it is highly suggested that authority intervention by translocating the long-tailed macaques elsewhere is necessary to avoid prolonged contact and possible parasite transmission to humans, and if any parasitic infections occur, appropriate medication such as anthelmintic drugs should be readily available at the university campus clinics.